Contribution of rare and potentially functionally relevant sequence variants in schizophrenia risk-Locus Xq28,distal - Claus, Isabelle; Sivalingam, S.; Koller, A. C.; Weiß, A.; Mathey, C. M.; Sindermann, L.; Klein, D.; Henschel, L.; Ludwig, K. U.; Hoffmann, P.; Heimbach, A.; Heilmann-Heimbach, S.; et al. (American journal of medical genetics. Part B, Neuropsychiatric genetics, 2025)
Duplications of the Xq28,distal locus have been described in male and female patients with schizophrenia (SCZ) or intellectual disability. The Xq28,distal locus spans eight protein-coding genes (F8, CMC4, MTCP1, BRCC3, VBP1, FUNDC2, CLIC2, and RAB39B) and is flanked by recurrent genomic breakpoints. Thus, the issue of which gene/s at this locus is/are relevant in terms of SCZ pathogenesis remains unclear. The aim of this study was to investigate the contribution of rare and potentially functionally relevant sequence variants within the Xq28,distal locus to SCZ risk using the single-molecule molecular inversion probes (smMIP) method. Targeted sequencing was performed in a cohort of 1935 patients with SCZ and 1905 controls of European ancestry. The consecutive statistical analysis addressed two main areas. On the level of the individual variants, allele counts in the patient and control cohort were systematically compared with a Fisher's exact test: (i) for the entire present study cohort; (ii) for patients and controls separated by sex; and (iii) in combination with data published by the Schizophrenia Exome Meta-Analysis (SCHEMA) consortium. On the gene-wise level, a burden analysis was performed using the X-chromosomal model of the Optimal Unified Sequence Kernel Association Test (SKAT-O), with adjustment for possible sex-specific effects. Targeted sequencing identified a total of 13 rare and potentially functional variants in four patients and 11 controls. However, neither at the level of individual rare and potentially functional variants nor at the level of the eight protein-coding genes at the Xq28,distal locus was a statistically significant enrichment in patients compared to controls observed. Although inconclusive, the present findings represent a step toward improved understanding of the contribution of X-chromosomal risk factors in neuropsychiatric disorder development, which is an underrepresented aspect of genetic studies in this field.
Online veröffentlicht: 30 October 2024
Gesehen am 18.08.2025